Pengaruh Modal Dan Umur Usaha Terhadap Pendapatan Umkm Di Kota Mataram - Yanti, Ni Wayan Ayu Yusvika; Effendy, Lukman; Astuti, Widia (Jurnal Riset Mahasiswa Akuntansi, 2025)
This study examines the effect of capital and business age on MSMEs income in Mataram City. Capital and business age are important factors that are thought to be able to determine the level of income of MSME actors. This study was conducted on 100 MSME actors in Mataram City using a quantitative approach and multiple linear regression methods as analysis tools. The results of the study indicate that capital and business age have a significant and positive effect on MSME income. This means that the greater the capital owned by MSME actors, the greater the income that can be obtained and the longer a business is run, the higher the income generated due to increased experience and business efficiency. This finding strengthens the theory of production which states that capital and skills (in this case represented by business age) are important factors in creating economic output. The implications of this study provide a warning signal that in order to increase income, MSME actors must pay attention to the availability of sufficient capital and long-term business sustainability. Local governments and related agencies are also advised to provide ongoing financing and training support as a form of more effective and sustainable MSMEs empowerment.